2020
DOI: 10.18203/2320-1770.ijrcog20203830
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women’s knowledge and practice of preventive measures against COVID-19: a study from Mysore city, Karnataka, India

Abstract: Background: The presently ongoing COVID-19 pandemic has not spared any segment of society including pregnant women. It is absolutely essential that pregnant mothers and their caregivers be fully aware of accurate facts about COVID-19. Objective of this study was to assess the knowledge and practice of preventive measures against COVID-19 infection among pregnant women of Mysore City.Methods: This was a cross sectional study, conducted among pregnant women attending prenatal care at a tertiary care centre. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Pregnant women should have good compliance with COVID-19 to prevent risk of contracting the virus and the adverse maternal and fetal outcomes from the virus. 36 , 37 This study revealed that 222 (56.1%) (95% CI: 51.8, 61.3) of pregnant women had good compliance with COVID-19 preventive measures which is lower than the studies conducted in Guraghe, Ethiopia 76.2%, 30 India (67.7–92.7%), 38 , 39 South Africa (76%), 40 and low-resource African settings (69.7%). 33 The possible variation might be the difference in socio-cultural and demographic characteristics, study setting, and study participants.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Pregnant women should have good compliance with COVID-19 to prevent risk of contracting the virus and the adverse maternal and fetal outcomes from the virus. 36 , 37 This study revealed that 222 (56.1%) (95% CI: 51.8, 61.3) of pregnant women had good compliance with COVID-19 preventive measures which is lower than the studies conducted in Guraghe, Ethiopia 76.2%, 30 India (67.7–92.7%), 38 , 39 South Africa (76%), 40 and low-resource African settings (69.7%). 33 The possible variation might be the difference in socio-cultural and demographic characteristics, study setting, and study participants.…”
Section: Discussionmentioning
confidence: 64%
“…This is supported by the study conducted in India, and Debre Tabor; educational status was associated with the level of Knowledge, attitude towards COVID-19 preventive measures and practice. 29 , 38 This could be due to an educated husband being likely to exposed to COVID-19 information via mass media, social media, and others; finally, will influence positively his wife to adhere to COVID-19 preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, to reduce the risk of infection in the antenatal participant population should carry further education should be carried out to convey the importance of observing recommended practices to reduce contractions and transmission of COVID-19. Research conducted by Shivanagappal [21], Awad et al [25], Nwafor et al [26], Aghababaei et al [27], Alemu Degu et al [28] also found that the knowledge of pregnant women about the transmission of COVID-19 was high. On the other hand, research conducted by Fikadu et al [29] and Ayele et al [30] found that the knowledge and practice of pregnant women regarding COVID-19 were poor.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge is a crucial thing in all areas of human endeavor. In the project of preventing and treating coronavirus infections, the community needs to know entirely and precisely about these new viral infections because misleading information spread through social media can lead the public to wrong actions [21]. It is crucial to increase knowledge, attitudes, and behavior in the general public, especially pregnant women, especially in the current period of rising cases of COVID-19 [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation